The US class action settlement agreement in Cobell v. Salazar: an adequate redress for 120 years of mismanagement of Indian lands and funds? - Göcke, Katja (International journal on minority and group rights, 2012)
In June 1996, five Indian beneficiaries filed a class action lawsuit on behalf of all present and past individual Indian trust beneficiaries against the US Department of the Interior and the Department of the Treasury for failing to properly manage and account for Indian trust assets, which have been held in trust by the US government for individual Indians since the end of the 19th century. On 7 December 2009, after thousands of court filings and over 80 published opinions, the parties settled the issue out of court by concluding the Cobell settlement agreement, which was subsequently endorsed by the US Congress and gained final approval from the competent court. According to the settlement agreement, the US government is obliged to pay USD 3.412 billion, thus making the Cobell settlement the largest settlement the US government has ever entered into.